Estrategias organizacionales para la reacción y el desarrollo empresarial de las micro y pequeñas empresas tras la pandemia (2020)
The COVID-19 pandemic has affected the social and economic life of the entire world population. In Colombia, the passage of the virus has devastated social, humanitarian and economic issues. Within this last effect, the engine of recent growth of the Colombian economy, retail, contracted by more than 30 percentage points according to the National Administrative Department of Statistics (DANE). This contraction has been caused by the relevant health measures in terms of social distancing and mobility restrictions. The guilds and associations of businessmen, merchants and industrialists have provided the primary consequences of the passage of these restrictions. However, the reaction measures and now reactivation have not been able to reach the entire Colombian business arm. This work proposes to work the organizational strategies beyond the fiscal and monetary by the state agents and give the guiding points from the organizational theory and the current situation for the micro, small and medium...